Analysis of Social Media’s Impact on the Behavior of Islamic Education Students at IAIN Kerinci - Sholha, Maulida; Putra, Pristian Hadi; Damni, Albertos (J-PAI: Jurnal Pendidikan Agama Islam, 2024)
Today's information and communication technology continues to develop, making it easier for everyone to find information or to communicate with others. In recent years, information and communication technology (ICT) has developed very rapidly. Currently, the development of information and communication technology (ICT) is rapidly advancing and extending into various aspects of life. The Internet of Things (IoT), artificial intelligence (AI), and 5G networks are some of the innovations driving this progress. The presence of these technologies enables broader connectivity, more sophisticated automation, and increased efficiency across various sectors, such as healthcare, education, business, and transportation. The use of social media and instant messaging applications is also becoming more widespread, making communication between individuals and groups easier and faster. The internet has also presented new innovations in technology, one of which is social media. social media, proven to be able to shape opinions, attitudes and behavior of the public or society. This study aims to determine the impact of social media on the behavior of Islamic Religious Education students IAIN Kerinci. This study uses a quantitative approach to determine the impact of social media use on the moral awareness of Islamic Religious Education students IAIN Kerinci. Data collection techniques used are questionnaires and questionnaires. The object of this research is students of Islamic Religious Education IAIN Kerinci. Data analysis used in this research is descriptive statistics. In the research, it was found that social media can have a greater positive impact on the behavior of Islamic Religious Education students at IAIN Kerinci. The negative impact is around 14.6% of 48 people who agreed with the statement, "Using social media makes me forget to fulfill my religious obligations."